An Analysis of the Mental Health Act, 2018 of Bangladesh: The Relationship between International Treaties and State Laws - Suvra, Anika Nower; Ontar, Md.Morshed Hossain (Nurani Hukum, 2024)
Every nation deals with distinct challenges, and deciding how to address or accept them can be complex. Mental health problems are particularly significant among these challenges. Despite increasing global awareness of mental health issues, there remains a notable lack of discussion about the immediate and long-term physical and emotional impacts experienced by individuals with mental health conditions. In Bangladesh, these issues are increasingly prevalent in families, communities, and workplaces, contributing to rising discrimination against people with mental disorders and making it challenging for them to protect their rights in society. The UDHR, ICCPR, ICESCR and CRPD, which advocates for mental health protections, questions how well domestic laws such as the Bangladesh Mental Health Act 2018 meet international standards. Efforts are underway to fully comply with this law, which, like any legislation, has both strengths and weaknesses. Consequently, this paper critically examines both perspectives, focusing on Bangladesh's current struggles to ensure the rights of those affected by mental health issues. The authors assess the broader implications of the Bangladesh Health Act 2018, scrutinizing its objectives, implementation strategies, and its effectiveness in addressing mental health concerns to ensure equitable treatment and uphold the essential legal rights within the country